Manajemen Sarana dan Prasarana Pendidikan dalam Membangun Budaya Sekolah Berkarakter - Nasywa Aulia Putri; Marsya Zahrina Sugiarti; Ahmad Faiz Ritonga (International Forum of Researchers and Lecturers, 2026)
Educational facilities and infrastructure do not only function as technical support for learning but also have a strategic role in shaping school culture and students’ character. However, the reality is that the provision of facilities and infrastructure in many schools has not always been accompanied by effective management, resulting in suboptimal contribution to character building. This article aims to analyze how the management of educational facilities and infrastructure including planning, procurement, utilization, maintenance, and supervision can support the development of a character-based school culture. The analysis integrates educational management theory, national education standards, and recent research from 2023-2025. The results indicate that facilities and infrastructure significantly contribute to character formation when managed systematically, participatively, and integrated with character education programs. This finding implies that school leaders and policymakers need to ensure an integrated management system that aligns infrastructure development with character education objectives to maximize its educational impact in schools.